Manajemen Kelas Berbasis Multiple Intelligences dan Digital di MA Pembangunan Yayasan Syarif Hidayatullah Jakarta - Mallika Insyirah Syngenta; Syifa Awaliah; Ighna Utsani Fitria; Vinna Tri Damayanti; Hilal Tafattuhil Arzaq; Dicky Anggriawan Nugroho (CV Edujavare Publishing, 2024)
Class management based on Multiple Intelligences (MI) and digital technology has become the main focus in improving the quality of learning at the Madrasah Aliyah (MA) Development of the Syarif Hidayatullah Foundation Jakarta. This research aims to explore the application of the MI approach and the integration of digital technology in classroom management, as well as its impact on student learning outcomes. The research results show that the implementation of MI-based classroom management has increased student involvement in learning and helped identify their individual potential. Teachers use a variety of learning strategies that suit students' various intelligences, such as project-based learning, group discussions, and creative activities. In addition, the integration of digital technology, such as the use of interactive learning software and social media, has enriched students' learning experiences and facilitated access to information more broadly